2023
DOI: 10.1039/d3nr02318d
|View full text |Cite
|
Sign up to set email alerts
|

Functional micro-RNA drugs acting as a fate manipulator in the regulation of osteoblastic death

Abstract: Osteoblastic death can be regulated by miRNAs. We propose a tetrahedral DNA nanostructure-based microRNA delivery system (Tmi) as an example of miRNA drugs application, which provides a new strategy for gene therapy in bone diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 145 publications
(211 reference statements)
0
1
0
Order By: Relevance
“…MiR-21 variation in pro-osteoclastogenesis is consistent with the upregulation of circulating miR-21 during ONJ progression [29,30]. The primary targets of miR-145 instead include interleukin (IL) and genes related to bone homeostasis, such as osteomodulin, cwcv, and kazal-like domains proteoglycan 2, SPARC/osteonectin, and secreted protein acidic and rich in cysteine [6,31,32]. Additionally, miR-21 showed a favorable link with the pathophysiology of particle-induced osteolysis, and its knockdown-restricted osteoclastogenesis.…”
Section: Mirnasmentioning
confidence: 66%
“…MiR-21 variation in pro-osteoclastogenesis is consistent with the upregulation of circulating miR-21 during ONJ progression [29,30]. The primary targets of miR-145 instead include interleukin (IL) and genes related to bone homeostasis, such as osteomodulin, cwcv, and kazal-like domains proteoglycan 2, SPARC/osteonectin, and secreted protein acidic and rich in cysteine [6,31,32]. Additionally, miR-21 showed a favorable link with the pathophysiology of particle-induced osteolysis, and its knockdown-restricted osteoclastogenesis.…”
Section: Mirnasmentioning
confidence: 66%
“…It is characterized membrane rupture by activating NLRP3/Caspase-1/GSDMD signaling, causing the excessive release of pro-inflammatory cytokines, mainly included IL-18 and IL-1β ( Shi, et al, 2015 ). Many research has reported that pyroptosis plays an important role in occurrence and development of osteoporosis ( Cai, et al, 2023 ; Fu, et al, 2023 ; Tao, et al, 2020b ). Osteoblasts are the main functional cells in bone formation, responsible for the synthesis, secretion and mineralization of bone matrix, which also plays an essential role in formation of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%